2022
DOI: 10.1371/journal.pone.0267814
|View full text |Cite
|
Sign up to set email alerts
|

PEGDA microencapsulated allogeneic islets reverse canine diabetes without immunosuppression

Abstract: Background Protection of islets without systemic immunosuppression has been a long-sought goal in the islet transplant field. We conducted a pilot biocompatibility/safety study in healthy dogs followed by a dose-finding efficacy study in diabetic dogs using polyethylene glycol diacrylate (PEGDA) microencapsulated allogeneic canine islets. Methods Prior to the transplants, characterization of the canine islets included the calculations determining the average cell number/islet equivalent. Following measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…Previous work by our group has shown that delivery of islet cells encapsulated in poly(ethylene) glycol-based hydrogel microspheres into a diabetic rodent model facilitated healthy blood glucose levels compared to an unencapsulated cell transplant control group [38]. This work demonstrates the value of hydrogel microsphere-mediated cell delivery for long-term applications where immunoprotection is essential for a successful transplant [34].…”
Section: Introductionmentioning
confidence: 56%
“…Previous work by our group has shown that delivery of islet cells encapsulated in poly(ethylene) glycol-based hydrogel microspheres into a diabetic rodent model facilitated healthy blood glucose levels compared to an unencapsulated cell transplant control group [38]. This work demonstrates the value of hydrogel microsphere-mediated cell delivery for long-term applications where immunoprotection is essential for a successful transplant [34].…”
Section: Introductionmentioning
confidence: 56%
“…The absence of immunosuppression reverses the signs of diabetes and leads to insulin-independent status or significantly reduced insulin requirements (119) Polyethylenglycol (PEG)…”
Section: Discussionmentioning
confidence: 99%